COMPARATIVE STUDY OF METABOLITES AND ANTIMICROBIAL ACTIVITIES OF ESSENTIAL OILS EXTRACTED FROM THREE AMOMUM SUBULATUM CULTIVARS: Isolation, chemical characterization, antimicrobial study of three Greater cardamom cultivars essential oils - AFTAB ALAM,; RITA SINGH MAJUMDAR,; PRAVEJ ALAM, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In Sikkim (India), Seremna is a highly growing cultivar of Amomum subulatum at lower altitudes. Other popular cultivated varieties are Varlangy and Sawney in the same state but at different altitude. In this study, we evaluate the variation in essential oils, metabolites and antimicrobial activities among A. subulatum selected cultivars. Methods: The composition of essential oil of Varlangy, Seremna, and Sawney was analyzed using gas chromatography–mass spectrometry and comparative antimicrobial activity of oils was explored using agar well diffusion and agar dilution method. Results: The Seremna cultivar oil was shown the high content of major constituents (1,8-cineole) in comparison to others. Comparative minimum inhibitory concentrations and minimal bactericidal concentration (MBC) or minimal fungicidal concentration against two Gram-positive (Staphylococcus aureus and Bacillus subtilis), two Gram-negative (Klebsiella pneumoniae and Escherichia coli) bacteria, and two (Candida albicans and Aspergillus niger) fungi were determined. The oil of Seremna showed distinct antibacterial and antifungal activity against all the microorganisms except B. subtilis which showed resistance. Conclusion: The present findings concluded that the high content of the principal compound accelerates the antimicrobial activity of essential oils. The essential oil of Seremna could be a good antimicrobial agent and recommended in the case of infections.